Android-Based Design of a Fresh Red Jabs (Jabs) Selling Application During the Covid-19 Virus Pandemic - Indriyawati; Ritzkal (Jurnal Pengabdian Nusantara, 2023)
Red guava is one of the crops from the Pamijahan sub-district, Bogor Regency. The current system is considered ineffective in terms of marketing, especially during a pandemic like this, buyers/customers want the convenience or speed of relevant information to facilitate all their activities without having to leave the house. The Covid-19 virus makes people anxious and afraid to leave the house. In dealing with this problem, researchers designed an Android-based mobile application with the prototype method to facilitate ordering or selling red guava transactions and conducting technology-based marketing. Meanwhile, the system uses the Unified Modeling Language in the analysis and design phase. From the test results, the system performance is running well.